Organosilicon anticorrosive paint for outdoor steel structure and preparation method thereof

By using α,ω-terminal hydroxy polydimethylsiloxane and modified vapor phase silica in silicone coatings, the contradiction between high strength, high elasticity and construction performance of the coating is solved, and a high-performance anticorrosion coating suitable for outdoor steel structures is achieved.

CN119752322APending Publication Date: 2025-04-04CHINA TOWER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411984164.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There are contradictions in existing silicone coatings when taking into account high strength, high elasticity and good construction performance, and the mechanical strength is low, making it difficult to meet the multiple performance requirements of outdoor steel structures for anticorrosion coatings.

Method used

α,ω-terminal hydroxy polydimethylsiloxane is used as the basic film forming substance, and is strengthened by the modified gas phase method, activated nano calcium carbonate, and wollastonite, and modified talc powder is used to improve elasticity to solve the problems of high strength, high elasticity and construction performance.

Benefits of technology

It realizes that silicone anticorrosion coatings have good weather resistance, water resistance, corrosion resistance, construction properties and high strength and elastic properties in outdoor steel structure applications, extending the service life of the steel structure and reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222187330000071
    Figure BDA0005222187330000071
Patent Text Reader

Abstract

The invention discloses an organosilicon anticorrosive paint for outdoor steel structures and a preparation method thereof, the paint comprises the following raw materials by weight: 300 parts of alpha, omega-hydroxyl-terminated polydimethylsiloxane, 20-30 parts of modified fumed silica, 20-30 parts of wollastonite, 100-150 parts of active calcium carbonate, 20-40 parts of modified talcum powder, 15-30 parts of a cross-linking agent, 5-10 parts of a coupling agent, 0.3-0.6 part of a catalyst, and 150 parts of a solvent. The preparation method comprises the following steps: uniformly mixing and stirring alpha, omega-hydroxyl-terminated polydimethylsiloxane, modified fumed silica, activated calcium carbonate and modified talcum powder, then adding wollastonite, continuously mixing and stirring, and kneading in vacuum to obtain a base material; the preparation method comprises the following steps: adding the cross-linking agent into the base material while stirring at room temperature, stirring, adding the coupling agent and the catalyst, uniformly mixing, vacuumizing, stirring, and adding the solvent after uniformly stirring, thereby obtaining the organic silicon anticorrosive paint for the outdoor steel structure. The obtained organic silicon coating has high strength, high elasticity, good constructability, weather resistance, water resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organosilicon coatings, and in particular to an organosilicon anticorrosive coating for outdoor steel structures and a preparation method thereof. Background Art

[0002] my country's outdoor infrastructure facilities include many steel structures, such as tower base stations, steel bridges, steel workshops, ship parts, solar brackets, etc., which are exposed to the natural environment for a long time and are easily affected by corrosion factors such as oxygen, ultraviolet rays, moisture, and chemicals. After a long period of wind and rain, they are prone to cracking and corrosion, which in turn affects their bearing capacity and service life, resulting in the need for frequent maintenance. At the same time, corrosion will not only lead to the decline of steel structure performance, but may also cause safety accidents.

[0003] Anti-corrosion coatings can effectively isolate these corrosive media and slow down the corrosion rate of steel structures, thereby extending their service life. By applying anti-corrosion coatings, structural damage caused by corrosion can be reduced, ensuring the safe use of buildings, and pollutant emissions caused by corrosion. Choosing anti-corrosion coatings with a longer service life can reduce the frequency of steel structure replacement and maintenance, thereby reducing long-term maintenance costs.

[0004] With the continuous advancement of science and technology, outdoor steel structure anti-corrosion coatings need to have good comprehensive performance in all aspects, including good weather resistance, water resistance, mechanical properties, workability, etc. Silicone coatings have good UV resistance, high and low temperature resistance, water resistance, good elasticity, etc. The outstanding feature is that they can effectively withstand outdoor ultraviolet rays, oxygen, and rain, and can achieve a durability of 10-15 years, which is unattainable by conventional acrylic and epoxy coatings. However, silicone coatings also have relatively low mechanical strength, especially high strength, high elasticity and good workability are difficult to take into account. Some steel structures are frequently subjected to stress, such as wind loads on telecommunication towers at high altitudes, car loads on steel bridges, sandstorms or hail in special climate areas, etc., which will cause the coating on its surface to be impacted by external forces or the rigid substrate to shake, and place high demands on the strength and elasticity of the coating. However, the characteristics of high strength and high elasticity often lead to performance contradictions. At the same time, silicone itself has low strength and needs to rely on reinforcing powders to achieve high strength properties. For example, fumed silica is a typical reinforcing filler. However, after reinforcement with this type of filler, it is easy to cause the viscosity of the coating to increase and the thixotropy of the coating to be too strong, resulting in construction difficulties. Even if more solvent is added to dilute and reduce the viscosity, it is difficult to reduce the thixotropy accordingly. Summary of the invention

[0005] The purpose of the present invention is to overcome one or more deficiencies in the existing formulation technology of silicone coatings, especially the contradiction between high strength, high elasticity and construction performance, and to provide a silicone anti-corrosion coating suitable for outdoor steel structures that has good weather resistance, waterproofness, corrosion resistance, construction performance and high strength and elasticity.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an organosilicon anti-corrosion coating for outdoor steel structures, wherein the raw materials, by weight, include 300 parts of α, ω-terminated hydroxyl polydimethylsiloxane, 20 to 30 parts of modified fumed silica, 20 to 30 parts of wollastonite, 100 to 150 parts of activated calcium carbonate, 20 to 40 parts of modified talc, 15 to 30 parts of a cross-linking agent, 5 to 10 parts of a coupling agent, 0.3 to 0.6 parts of a catalyst, and 150 parts of a solvent.

[0007] On the other hand, the present technical solution provides a method for preparing an organosilicon anti-corrosion coating for outdoor steel structures, comprising the following steps:

[0008] Step 1: Mix α,ω-terminated hydroxyl-terminated polydimethylsiloxane, modified fumed silica, activated calcium carbonate and modified talc and stir them evenly, then add wollastonite, continue to mix and stir, and knead under vacuum to obtain a base material;

[0009] Step 2: Add the cross-linking agent to the base material under stirring at room temperature, then add the coupling agent and the catalyst, mix well, evacuate and stir, add the solvent after stirring well, and obtain the organosilicon anti-corrosion coating for outdoor steel structure.

[0010] Preferably, as an improvement, the steps for preparing the modified fumed silica are:

[0011] S1, stirring and drying the fumed silica;

[0012] S2, diluting hexamethyldisilazane with toluene and spraying it on the surface of fumed silica, stirring and mixing;

[0013] S3, heating and vacuum drying.

[0014] Preferably, as an improvement, in step S1, the stirring and drying conditions are stirring and drying at 110°C for 2 hours; in step S2, the concentration of hexamethyldisilazane with toluene is 20%, and the mass ratio of hexamethyldisilazane to toluene vapor phase silica is 1:100; in step S3, the temperature is 150°C and the vacuum drying time is 2 hours.

[0015] Preferably, as an improvement, the specific surface area of ​​the fumed silica before modification is 200 m 2 / g.

[0016] Preferably, as an improvement, the preparation method of modified talcum powder comprises the following steps:

[0017] S1, stirring and drying talcum powder;

[0018] S2, diluting dodecyltrimethoxysilane with toluene and spraying it on the surface of fumed silica, stirring and mixing, the mass ratio of dodecyltrimethoxysilane with toluene to talc is 1:100;

[0019] S3, heating and vacuum drying.

[0020] Preferably, as an improvement, the α,ω-terminated hydroxyl-polydimethylsiloxane is a mixture of α,ω-terminated hydroxyl-polydimethylsiloxanes with viscosities of 5000mPa.s, 15000mPa.s, and 50000mPa.s in a mass ratio of 10:4:1; the active nano-calcium carbonate D50=500nm; and the solvent is D30 solvent oil.

[0021] Preferably, as an improvement, the crosslinking agent is at least one of tetrabutyl ketone oxime silane, methyl tributyl ketone oxime silane, vinyl tributyl ketone oxime silane, methyl triacetone oxime silane, methyl triisobutyl ketone oxime silane, methyl triacetoxy silane, methacryloxypropyl trimethoxy silane, polymethyl triisobutyl ketone oxime silane, and polymethyl triacetoxy silane; the coupling agent is at least one of γ-aminopropyl trimethoxy silane, γ-aminopropyl triethoxy silane, glycidyl ether oxygen propyl trimethoxy silane, methacryloxypropyl trimethoxy silane, methacryloxypropyl triethoxy silane, isocyanate propyl trimethoxy silane, vinyl trimethoxy silane, and vinyl triethoxy silane.

[0022] Preferably, as an improvement, the catalyst is at least one of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide, dibutyltin diacetate, stannous octoate, butyl titanate, and isopropyl titanate.

[0023] Preferably, as an improvement, in step one, the kneading conditions are 130° C. high temperature and -0.09 MPa vacuum for 3 hours; in step two, the vacuum stirring time is 10 minutes.

[0024] The principle and beneficial effects of this solution are as follows: In this technical solution, in view of the problem that the high strength, high elasticity and good construction performance of the organosilicon anticorrosion coating existing in the existing technical route are difficult to take into account, the present invention provides a type of technical route: using α, ω-terminated hydroxyl polydimethylsiloxane as the basic film-forming material, and reinforcing it together through modified fumed silica, active nano calcium carbonate and wollastonite; at the same time, wollastonite reduces the viscosity and thixotropy of the coating; modified talcum powder improves elasticity, which solves the contradiction that the high strength, high elasticity and good construction performance of the organosilicon anticorrosion coating are difficult to take into account, and the anticorrosion coating also has good weather resistance, waterproofness and corrosion resistance. In terms of formula composition: fumed silica is an excellent silicone rubber reinforcing nanofiller, but because the Si-OH group on the surface of silica easily forms hydrogen bonds with water, the silica particles are very easy to adsorb water molecules, which reduces its compatibility with silicone rubber. Therefore, in order to reinforce silicone rubber with fumed silica, it is first necessary to modify its surface and remove some Si-OH groups to increase the compatibility between the two. This is the key to giving silicone coatings high strength. In addition, during the research and development process, the inventors found that the amount of modified fumed silica added has a certain correlation with the performance of the material. If too much modified fumed silica is added, although it can give the material a higher strength, it will also significantly increase its viscosity and thixotropy, which will affect the coating construction performance. Therefore, an appropriate amount of modified fumed silica is taken, and semi-reinforcing fillers such as active nano-calcium carbonate and wollastonite are added for joint reinforcement. Since no excessive fumed silica is added, and wollastonite has a certain effect of reducing viscosity and thixotropy, the coating has high strength and good construction properties. At the same time, on the basis of reinforcing fillers such as fumed silica, the use of large-sized flake talcum powder inserted into the system can improve its elasticity, and the use of silane modification on its surface can improve its compatibility with the system, so that it can improve the elasticity of the coating without negatively affecting its strength, and make the coating have both high strength and high elasticity. Through the modification and reasonable matching of several types of fillers, an organosilicon anti-corrosion coating with excellent comprehensive performance can be obtained to meet the use requirements of outdoor steel structure facilities. DETAILED DESCRIPTION

[0025] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0026] Program Overview:

[0027] A silicone anti-corrosion coating for outdoor steel structures. The raw materials, measured by weight, include 300 parts of α, ω-terminated hydroxyl polydimethylsiloxane, 20-30 parts of modified fumed silica, 20-30 parts of wollastonite, 100-150 parts of activated calcium carbonate, 20-40 parts of modified talc, 15-30 parts of a cross-linking agent, 5-10 parts of a coupling agent, 0.3-0.6 parts of a catalyst and 150 parts of a solvent.

[0028] The α,ω-terminated hydroxyl polydimethylsiloxane is prepared by mixing α,ω-terminated hydroxyl polydimethylsiloxanes with viscosities of 5000mPa.s, 15000mPa.s, and 50000mPa.s in a mass ratio of 10:4:1.

[0029] The specific surface area of ​​fumed silica before modification is 200m 2 / g, the preparation steps of modified fumed silica are as follows: add 100 parts of fumed silica into a power mixer, stir and dry at 110°C for 2 hours; dilute 1 part of hexamethyldisilazane with toluene to 20%, spray evenly on the surface of the powder, continue to stir and mix at 110°C for 60 minutes. Heat to 150°C, vacuum dry for 2 hours, and seal for storage.

[0030] Active nano calcium carbonate D50=500nm.

[0031] The fineness of unmodified talcum powder is 800 mesh, and the preparation method of modified talcum powder comprises the following steps: adding 100 parts of talcum powder (100 mesh) into a power mixer, stirring and drying at 110° C. for 2 hours; diluting 1 part of dodecyltrimethoxysilane with toluene to 20%, spraying evenly on the surface of the powder, and continuing to stir and mix at 110° C. for 60 minutes. Heating to 150° C., vacuum drying for 2 hours, and sealing and storing for standby use.

[0032] The crosslinking agent is at least one of tetrabutyl ketoxime silane, methyl tributyketoxime silane, methyl trimethoxy silane, methyl triethoxy silane, vinyl triethoxy silane, methacryloxypropyl trimethoxy silane and ethyl orthosilicate.

[0033] The coupling agent is at least one of glycidyloxypropyl trimethoxysilane, methacryloxypropyl trimethoxysilane, methacryloxypropyl triethoxysilane, diethylaminomethyl triethoxysilane, aminopropyl trimethoxysilane, aminopropyl triethoxysilane, aminopropyl methyl diethoxysilane, aminopropyl methyl triethoxysilane and N-phenyl-3-aminopropyl trimethoxysilane.

[0034] At least one of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide, dibutyltin diacetate, stannous octoate, butyl titanate, and isopropyl titanate.

[0035] The solvent is D30 solvent oil.

[0036] A method for preparing an organosilicon anticorrosive coating for outdoor steel structures comprises the following steps:

[0037] Step 1: Mix α,ω-terminated hydroxyl-terminated polydimethylsiloxane, modified fumed silica, activated calcium carbonate and modified talc for 20 minutes, then add wollastonite, continue mixing and stirring for 10 minutes, and then knead at 130°C and 0.09Mpa vacuum for 3 hours to obtain a base material;

[0038] Step 2: Add the cross-linking agent to the base material under stirring at room temperature and stir for 10 minutes, then add the coupling agent and catalyst, mix well and stir in a vacuum for 10 minutes, add the solvent after stirring well, stir at normal pressure for 5 minutes and then discharge and package.

[0039] Example 1

[0040] A method for preparing an organosilicon anticorrosive coating for outdoor steel structures comprises the following steps:

[0041] 200 parts of α,ω-terminated hydroxyl polydimethylsiloxane with a viscosity of 5000mPa.s, 80 parts of α,ω-terminated hydroxyl polydimethylsiloxane with a viscosity of 20000mPa.s, 20 parts of α,ω-terminated hydroxyl polydimethylsiloxane with a viscosity of 50000mPa.s, 30 parts of modified fumed silica, 100 parts of activated calcium carbonate, and 40 parts of modified talc were mixed and stirred evenly for 20 minutes, and then 30 parts of wollastonite was added and the mixture was continued to mix. Stir for 10 minutes, then knead for 3 hours at 130℃ high temperature-0.09Mpa vacuum to obtain the base material; add 15 parts of methyl tributylacetoximosilane and 15 parts of vinyl tributylacetoximosilane to the base material under stirring at room temperature, stir for 10 minutes, then add 5 parts of γ-aminopropyl trimethoxysilane and 0.5 parts of dibutyltin dilaurate, mix well, vacuum and stir for 10 minutes, stir well, add 150 parts of D30 oil, stir at normal pressure for 5 minutes, and then discharge and package.

[0042] The specific surface area of ​​fumed silica before modification is 200m 2 / g, the preparation steps of modified fumed silica are:

[0043] Add 100 parts of fumed silica to a power mixer and stir and dry at 110°C for 2 hours. Dilute 1 part of hexamethyldisilazane with toluene to 20%, spray evenly on the powder surface, and continue stirring and mixing at 110°C for 60 minutes. Heat to 150°C, vacuum dry for 2 hours, and seal for storage.

[0044] The fineness of unmodified talcum powder is 800 mesh, and the preparation steps of modified talcum powder are as follows:

[0045] Add 100 parts of talc powder into a power mixer and stir and dry at 110°C for 2 hours. Dilute 1 part of γ-methacryloxypropyltrimethoxysilane to 20%, spray evenly on the surface of the powder, and continue stirring and mixing at 110°C for 60 minutes. Heat to 150°C and vacuum dry for 2 hours, seal and store for later use.

[0046] Example 2

[0047] The cross-linking agent in Example 1 was replaced by 15 parts of methyl tributylacetoximine silane and 15 parts of vinyl tributylacetoximine silane with 10 parts of tetrabutyl ketoxime silane and 10 parts of polymethyltriacetoxysilane; the coupling agent was replaced by 5 parts of aminopropyltrimethoxysilane with 5 parts of γ-aminopropyltriethoxysilane and 1 part of glycidyloxypropyltrimethoxysilane; the catalyst was replaced by 0.5 parts of dibutyltin dilaurate with 0.3 parts of butyl titanate, 20 parts of modified fumed silica, 150 parts of activated calcium carbonate, 20 parts of modified talc, and 20 parts of wollastonite. The other formulas and steps are the same as those in Example 1.

[0048] Comparative Example 1

[0049] The modified fumed silica in the coating formula of Example 1 was replaced with the same mass fraction of activated calcium carbonate, and the other formulas and steps were the same.

[0050] Comparative Example 2

[0051] The modified fumed silica in the coating formulation in Example 1 was replaced with unmodified fumed silica of the same mass fraction, and the other formulations and steps were the same.

[0052] Comparative Example 3

[0053] The wollastonite in the coating formula in Example 1 was replaced with activated calcium carbonate of the same mass fraction, and the other formulas and steps were the same.

[0054] Comparative Example 4

[0055] The wollastonite in the coating formulation in Example 1 was replaced with the same amount of modified fumed silica, and the other formulations and steps were the same.

[0056] Comparative Example 5

[0057] The modified talc in the finished coating formulation in Example 1 was replaced with activated calcium carbonate of the same mass fraction, and the other formulations and steps were the same.

[0058] Comparative Example 6

[0059] The modified talcum powder in the finished coating formula of Example 1 was replaced with unmodified talcum powder of the same mass fraction, and the other formulas and steps were the same.

[0060] Experimental Example Performance Test

[0061] The performance test indicators and test methods for the coating in the embodiments of the present invention are as follows:

[0062] The construction performance, salt spray resistance, water resistance, acid resistance, artificial aging resistance and temperature change resistance are tested in accordance with the standard JG / T 224-2007 Anti-corrosion coatings for building steel structures.

[0063] The viscosity was tested using a rotational viscometer under standard conditions, namely, temperature (23±2)°C and relative humidity (50±5)%.

[0064] The thixotropic index is calculated based on the apparent viscosity η6 at a rotation speed of 6 rpm and the apparent viscosity η at a rotation speed of 60 rpm. 60 Calculation yields: It = η6 / η 60 .

[0065] The tensile strength and elongation at break are tested in accordance with JG / T 512-2017 General Technical Requirements for Building Exterior Wall Paints.

[0066] The test results of the coating properties of each embodiment and comparative example are shown in Table 1, and each group was tested three times.

[0067] Table 1 Performance test results of embodiments and comparative examples

[0068]

[0069] As can be seen from the data in Table 1, compared with Example 1, after the modified fumed silica is replaced with active nano-calcium carbonate, the tensile strength of Comparative Example 1 is significantly reduced, indicating that the modified fumed silica is very important for the high strength of the coating, and at the same time, the viscosity and thixotropy are significantly reduced, and the reduction in its elongation at break indicates that although the modified fumed silica is not the main factor affecting the elasticity of the coating, the overall change in the filler combination will have an impact on the elasticity of the coating. The corresponding coating strength, viscosity and thixotropy index of Comparative Example 2 relative to Example 1 also decrease, which may be due to the surface modification of fumed silica that strengthens its compatibility with the silicone rubber matrix. The performance change of Comparative Example 3 relative to Example 1 shows that the reinforcing effect of wollastonite is not strong, but it is beneficial to reduce the viscosity and thixotropy index of the system after adding it, that is, to improve the construction property. Comparative Example 4 relative to Example 1 and Comparative Example 3, it is explained that although increasing the amount of modified fumed silica can greatly improve the strength of the coating, it will significantly increase the viscosity and thixotropy index, which is not conducive to the construction property of the coating. The performance change of Comparative Example 5 relative to Example 1 shows that the application of modified talc in the system can significantly increase the elongation at break and improve the elasticity of the coating. The performance change of Comparative Example 6 relative to Example 1 shows that the modification of talc is beneficial to improving the strength and elongation of the coating, which may be due to the silane modification improving the compatibility of talc and silicone rubber film-forming material.

[0070] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. An organosilicon anticorrosive coating for outdoor steel structures, characterized in that: The raw materials, measured by weight, include 300 parts of α,ω-terminated hydroxyl polydimethylsiloxane, 20-30 parts of modified fumed silica, 20-30 parts of wollastonite, 100-150 parts of activated calcium carbonate, 20-40 parts of modified talc, 15-30 parts of a crosslinking agent, 5-10 parts of a coupling agent, 0.3-0.6 parts of a catalyst, and 150 parts of a solvent.

2. The organic silicon anticorrosive coating for outdoor steel structure according to claim 1, characterized in that: The modified fumed silica preparation steps are: S1, stirring and drying the fumed silica; S2, diluting hexamethyldisilazane with toluene and spraying it on the surface of fumed silica, stirring and mixing; S3, heating and vacuum drying.

3. The organic silicon anticorrosive coating for outdoor steel structure according to claim 2, characterized in that: In step S1, the stirring and drying conditions are stirring and drying at 110° C. for 2 hours; in step S2, the concentration of hexamethyldisilazane with toluene is 20%, and the mass ratio of hexamethyldisilazane with toluene vapor phase silica is 1:100; in step S3, the temperature is 150° C. and the vacuum drying time is 2 hours.

4. The organic silicon anticorrosive coating for outdoor steel structure according to claim 3, characterized in that: The specific surface area of ​​the fumed silica before modification is 200 m 2 / g.

5. The organic silicon anticorrosive coating for outdoor steel structure according to claim 4, characterized in that: The preparation method of the modified talcum powder comprises the following steps: S1, stirring and drying talcum powder; S2, diluting dodecyltrimethoxysilane with toluene and spraying it on the surface of fumed silica, stirring and mixing, the mass ratio of dodecyltrimethoxysilane with toluene to talc is 1:100; S3, heating and vacuum drying.

6. The organic silicon anticorrosive coating for outdoor steel structure according to claim 5, characterized in that: The α,ω-terminated hydroxyl polydimethylsiloxane is prepared by mixing α,ω-terminated hydroxyl polydimethylsiloxanes with viscosities of 5000mPa.s, 15000mPa.s and 50000mPa.s in a mass ratio of 10:4:1; the active nano calcium carbonate D50 is 500nm; and the solvent is D30 solvent oil.

7. The organosilicon anticorrosive coating for outdoor steel structure according to claim 6, characterized in that: The cross-linking agent is at least one of tetrabutyl ketone oxime silane, methyl tributyketone oxime silane, vinyl tributyketone oxime silane, methyl triacetone oxime silane, methyl triisobutyl ketone oxime silane, methyl triacetoxy silane, methacryloxypropyl trimethoxy silane, polymethyl triisobutyl ketone oxime silane, and polymethyl triacetoxy silane; the coupling agent is at least one of γ-aminopropyl trimethoxy silane, γ-aminopropyl triethoxy silane, glycidyl ether oxypropyl trimethoxy silane, methacryloxypropyl trimethoxy silane, methacryloxypropyl triethoxy silane, isocyanate propyl trimethoxy silane, vinyl trimethoxy silane, and vinyl triethoxy silane.

8. The organic silicon anticorrosive coating for outdoor steel structure according to claim 7, characterized in that: The catalyst is at least one of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide, dibutyltin diacetate, stannous octoate, butyl titanate and isopropyl titanate.

9. The method for preparing an organosilicon anticorrosive coating for outdoor steel structure according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Mix α,ω-terminated hydroxyl-terminated polydimethylsiloxane, modified fumed silica, activated calcium carbonate and modified talc and stir them evenly, then add wollastonite, continue to mix and stir, and knead under vacuum to obtain a base material; Step 2: Add the cross-linking agent to the base material under stirring at room temperature, then add the coupling agent and the catalyst, mix well, evacuate and stir, add the solvent after stirring well, and obtain the organosilicon anti-corrosion coating for outdoor steel structure.

10. The method for preparing an organosilicon anticorrosive coating for outdoor steel structure according to claim 9, characterized in that: In step 1, the kneading conditions are 130° C. high temperature and -0.09 MPa vacuum for 3 h; in step 2, the vacuum stirring time is 10 min.

Citation Information

Patent Citations

  • Elastic anti-corrosion coating

    CN101747835A

  • Organosilicon pressure-sensitive adhesive and product and preparation method thereof

    CN115181542A

  • Low-permeable-rate two-component-mass-part organic silica gel composition

    CN117126539A

  • Composition containing metallocene polyethylene and application of composition in silage film

    CN117820753A